Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.7 Separable first-order differential equations

Next we consider a type of differential equation called separable. The following equation appears to be an impossible case since we are mixing up xx and yy terms on the right:

dydx=y2(x2+1).\frac{dy}{dx}=y^{2}(x^{2}+1).

But we can transfer the yy terms to the left-hand side to obtain 1y2dydx=(x2+1).{\frac{1}{y^{2}}\frac{dy}{dx}=(x^{2}+1).} Now the left-hand side is just ddx(-1y)\frac{d}{dx}\left({\frac{-1}{y}}\right), by the chain rule. Thus the equation has been converted to: ddx(-1y)=x2+1.{\frac{d}{dx}\left(\frac{-1}{y}\right)=x^{2}+1.} This is an integrable equation! The general solution is given by integrating the left- and right-hand sides to obtain

-1y=x33+x+cy=-3x3+3x+c.\frac{-1}{y}={\frac{x^{3}}{3}+x+c}\;\;\Rightarrow y={\frac{-3}{x^{3}+3x+c^{% \prime}}.}